Efforts of Islamic Religious Education Teachers in Shaping the Personality of Muslim Students at SDIT Insan Utama Kasihan - Fanani, Istiqlal Yul; Shiddiq, Nurhidayah; Gligorovic, Milica; Bissessar, Charmaine (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
This study aims (1) to determine the personality condition of students at SDIT Insan Utama Kasihan, (2) to find out the efforts of Islamic religious education teachers in shaping the Muslim personality of students at SDIT Insan Utama Kasihan, (3) and to find out the inhibiting and supporting factors of Islamic religious education teachers in shaping the Muslim personality of students at SDIT Insan Utama Kasihan. This research uses a qualitative approach. His research method is a descriptive method. The data collection technique uses interview, documentation, and observation methods. The data analysis technique is the author using miles and huberman model analysis. The results of this study are (1) The personality of students at SDIT Insan Utama Kasihan is generally good, although there are still some children who behave poorly such as eating while standing, eating with their left hand, saying rude words, and littering. The personality of the students in this school, when viewed in terms of their creed, is very emphasized by their religion. When viewed in terms of worship, this school teaches its students to pray 5 times, dhuha prayers, tahajud prayers, and sunnah fasting. Furthermore, when viewed in terms of student morals, in this school, it is generally good. (2) The efforts of Islamic agam education teachers in shaping the Muslim personality of students at SDIT Insan Utama Kasihan, namely by fostering students' faith and piety to Allah SWT, directing students in the implementation of worship in schools, guiding students to have good morals, motivating students to actively study, and motivating students to aspire to the world and the Hereafter. (3) Factors inhibiting Islamic religious education teachers in shaping the muslim personality of students are the different levels of understanding of children and the lack of continuity between programs in schools and parents at home. Supporting factors are the religious school environment, the cooperation between Islamic religious education teachers and other teachers, and the existence of school programs that support the formation of students' personalities.